PENGARUH KECAKAPAN MANAJERIAL TERHADAP MANAJEMEN LABA AKRUAL DAN RIIL - Melinda Majid; Shanti Lysandra; Indah Masri; Widyaningsih Azizah (Jurnal Ilmiah Akuntansi dan Manajemen, 2020)
The purpose of this research is to examine the effect of managerial ability on accrual and real earnings management. The population in this research is companies listed in LQ45 index for the year 2016-2018. The sample is determined by purposive sampling method and obtained a sample of 25 companies. The type of data is secondary data obtained from www.idx.co.id. The analytical technique used in this research is panel data regression analysis and processed using the Eviews 9.0 program. The results indicated that managerial ability which is measured using Data Envelopment Analysis (DEA) has positive effect on accrual earnings management. However, managerial ability has negative effect on real earnings management. This is because there is a substitution relationship between accrual and real earnings management, when accrual earnings management increases, real earnings management will decrease